Xerostomia Severity and Quality of Life After Nasopharyngeal Cancer Radiotherapy: Intensity Modulated vs Two-dimensional Radiation Therapy in Indonesia - Soehartati Argadikoesoema Gondhowiardjo; Nikrial Dewin; Andreas Ronald; Vito Filbert Jayalie; Handoko Handoko; Sri Mutya Sekarutami; Zanil Musa (Radioterapi & Onkologi Indonesia, 2020)
Introduction: Two-dimensional technique (2DRT) is most commonly used in Indonesia. This technique causes severe late toxicity particularly in nasopharyngeal cancer (NPC). Radiation techniques such as Intensity-Modulated Radiation Therapy (IMRT) and Three-Dimensional Conformal Radiation Therapy (3DCRT) provide larger doses at the site of NPC while preserving normal tissue. This study aims to compare late side effects and quality of life (QoL) between IMRT and 2DRT groups.Method: This was a cross-sectional study with consecutive sampling. Salivae samples were collected at least 6 months after last radiation date. Xerostomia severity were determined by measuring whole saliva flow rate which then categorized based on Common Terminology Criteria for Adverse Events (CTCAE). European Organization for Research and Treatment of Cancer (EORTC) core questionnaire and EORTC head and neck module (QLQ-H&N35) wereused to assess QoL.Result: The IMRT group had higher saliva flow rate than 2DRT group (1,085 ±0,409 vs  0,188 ± 0,219 stimulated, 0,500±0,254 vs 0,196 ±0,156 unstimulated, p<0.001). According to CTCAE, IMRT group experienced less  grades 2 and 3 of xerostomia compared to 2DRT group (p<0.05). Moderate correlation between recovery time and saliva flow rate (p<0.05) was found in IMRT group at least 6 months after last radiation date. QLO-C30 scores were higher in IMRT group than those in 2DRT group, particularly in global health status, physical functioning, emotional functioning, pain and insomnia (p<0.05). IMRT group scored better in several QLQ-H&N35 subscales namely head and neck pain, swallowing, speech problems, trouble with social eating, trouble with social contact, dry mouth (p<0.05) and sticky saliva (p<0.001).Conclusion: IMRT was significantly superior to 2DRT in preserving and sparing the salivary gland especially parotid and improving quality of life .Thus, we recommend to treat NPC cases in Indonesia with IMRT to reduce toxicity of the treatment and improve quality of life, as it commonly affects people at productive age.